2018
DOI: 10.3390/rs10060859
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Satellite-Derived Bathymetry (SDB) with the Google Earth Engine and Sentinel-2

Abstract: Bathymetry mapping forms the basis of understanding physical, economic, and ecological processes in the vastly biodiverse coastal fringes of our planet which are subjected to constant anthropogenic pressure. Here, we pair recent advances in cloud computing using the geospatial platform of the Google Earth Engine (GEE) with optical remote sensing technology using the open Sentinel-2 archive, obtaining low-cost in situ collected data to develop an empirical preprocessing workflow for estimating satellite-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
137
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(165 citation statements)
references
References 38 publications
2
137
0
1
Order By: Relevance
“…Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20]. However, our temporal compositing strategy successfully reduced the turbidity impact without requirement of visual inspection, thereby enhancing SDB performance in an easy way.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas some researchers suggested there is still work to be performed regarding the identification of the optimal period throughout the year where bathymetric errors are minimized [18,29], others asked for novel strategies to allow seabed mapping without the laborious analysis per image and the visual inspection of the "clearest scene" [19]. Recent studies have already indicated the potential of multi-scene approaches in order to select the optimal scene or eliminate noise over clear waters [16,17,19,20]. However, our temporal compositing strategy successfully reduced the turbidity impact without requirement of visual inspection, thereby enhancing SDB performance in an easy way.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our findings, the portability and reliability application of the proposed approach using minimum in-situ measurements is a distinct advantage in effectiveness and may especially benefit developing countries. In addition, using the semi-automated solution and a computer cloud-based system may allow exploitation of the Sentinel-2 data for regional to global scale coastal SDB [16]. The average time required for processing a Sentinel-2 image for bathymetry estimation is 1 hour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All images were the top of atmosphere (TOA) reflectance. Landsat and Sentinel-2 TOA data have been widely used for remote sensing monitoring in previous studies [38,60,61]; for example, Dong et al [41] mapped paddy rice planting areas in northeastern Asia with Landsat-8 TOA images. Additionally, the Google Earth Engine has cloud-mask model codes for Landsat and Sentinel-2 TOA data production and, thus, we can easily remove the pixels which were covered with clouds.…”
Section: Composite Landsat and Sentinel Imagerymentioning
confidence: 99%
“…The first step in atmospheric correction procedure is the division of satellite image values with quantification value of 1000 to obtain TOA reflectance [16]. TOA reflectance is the amount of reflectance reflected off the surface which can be collected using a satellite sensor.…”
Section: Atmospheric Correctionsmentioning
confidence: 99%